A Companion to the History of the Roman Curia - Prudlo, Donald S. (Brill's Companions to the Christian Tradition, 2025)
The Roman Curia is the oldest extant body of institutional administration in the world. Indeed, it was the prototype for the development of centralized government in the monarchies of the Middle Ages. Further, it was the administrative backbone of the first worldwide organization in human history. It developed policies, laws, and procedures that continue to affect the entire world. This book offers scholarly contributions from the origins of the Curia to the early Modern period.